دور أساليب الاتصال التنظيمي في تحسين الكفاءة المهنية للأستاذ الجامعي دراسة ميدانية على عينة من أساتذة كلية العلوم الانسانية والاجتماعية بجامعة محمد الشريف مساعدية- سوق أهراس - ذكرى أسماء زوقاري; شادلية عجايلية (My University, 2025)
Abstract This study aimed to identify the actual professional competence of teachers at the Faculty of Humanities and Social Sciences, the nature of the communication styles they use, their effectiveness, and the obstacles that hinder this effectiveness. To do this, it attempted to answer the following central question: What is the role of communication styles in improuvent the professional competence of teachers at the Faculty of Humanities and Social Sciences at Souk Ahras University? This central question was broken down into several sub-questions: - What is the actual professional competence of teachers at the Faculty of Humanities and Social Sciences at Souk Ahras University? - What is the nature of the communication styles used by teachers at the Faculty of Humanities and Social Sciences at the University? - How effective are the communication styles used by teachers at the Faculty? - What are the obstacles that hinder the effectiveness of communication styles in achieving the professional competence of teachers at the Faculty? This study was based on the constructivist-functionalist theoretical approach, considered the most relevant for the study of our topic. To achieve the objective of this study, we used the descriptive method, due to its suitability for the research problem and its relevance for the collection, quantitative and qualitative analysis, and interpretation of data in their specific context. This method employed a set of tools including an electronic questionnaire based on an attitude scale, divided into four axes, as well as a sociodemographic information axis, and an observation tool. After statistical and descriptive analysis, a set of important results was obtained, the main ones being: - Average professional competence is present, with weaknesses in monitoring scientific developments and the use of technology. - Formal styles and electronic communication are the most widely used. Informal communication has a limited impact. – - Communication styles, particularly formal and technological, are highly effective in enhancing professional competence. - Psychological, organizational, and technical barriers significantly affect communication effectiveness and the achievement of competence. ---------------------------------- ملخص الدراسة هدفت هذه الدراسة الى التعرف على واقع الكفاءة المهنية لدى اساتذة كلية العلوم الانسانية والعلوم الاجتماعية وعلى طبيعة الاساليب الاتصالية المستخدمة عندهم ومدى فعاليتها والتعرف على المعوقات التي تقف امام فعاليتها. من خلال الاجابة على التساؤل المحوري التالي: ما دور الاساليب الاتصالية في تحسين الكفاءة المهنية للأساتذة في كلية العلوم الانسانية والعلوم الاجتماعية بجامعة سوق اهراس والتي تتمحور ضمنه مجموعة من الاسئلة الفرعية وهي: - ما هو واقع الكفاءة المهنية لدى اساتذة كلية العلوم الاجتماعية والعلوم الانسانية بجامعة سوق اهراس؟ - ما هي طبيعة الاساليب الاتصالية المستخدمة لدى اساتذة كلية العلوم الاجتماعية والعلوم الانسانية بالجامعة؟ - ما مدى فعالية اساليب الاتصال المستخدمة لدى اساتذة كلية العلوم الاجتماعية والعلوم الانسانية بالجامعة؟ - ما هي المعوقات التي تقف حائلا امام فعالية الاساليب والاتصالية في تحقيق الكفاءة المهنية لدى الاساتذة الكلية؟ تم الاعتماد في هذه الدراسة على المقاربة النظرية البنائية الوظيفية كونها الاقرب لدراسة موضوعنا. من اجل تحقيق هدف هذه الدراسة استخدمنا المنهج الوصفي لتناسبه مع اشكالية الدراسة وباعتباره الاقرب لجمع البيانات وتحليلها كميا وكيفيا وتفسيرها في سياقها المحدد بتوظيف مجموعة ادوات هي استمارة الكترونية بقالب قياس اتجاه التي تضم اربعة محاور مع محور المعلومات السوسيوغرافية وأداة الملاحظة. بعد المعالجة الاحصائية والوصفية تم التوصل الى مجموعة نتائج أهمها: - توجد كفاءة مهنية متوسطة، مع نقاط ضعف في متابعة التطورات العلمية واستخدام التكنولوجيا. - الأساليب الرسمية والاتصال الإلكتروني هما الأكثر استخدامًا. الاتصال غير الرسمي محدود الأثر. - الأساليب الاتصالية، خاصة الرسمية والتكنولوجية، فعالة جدًا في تعزيز الكفاءة المهنية. - المعوقات النفسية والتنظيمية والتقنية تؤثر بشكل كبير على فعالية الاتصال وتحقيق الكفاء ---------------------------------------------- Résumé de l'étude : Cette étude visait à identifier la réalité de la compétence professionnelle des professeurs de la Faculté des sciences humaines et sociales, la nature des moyens de communication qu'ils utilisent, leur efficacité et les obstacles qui entravent leur efficacité. En répondant à la question centrale suivante : Quel est le rôle des méthodes de communication dans l'amélioration de la compétence professionnelle des professeurs de la Faculté des Sciences Humaines et Sociales de l'Université Souk Ahras, qui s'articule autour d'un ensemble de sous-questions, à savoir : - Quelle est la réalité de la compétence professionnelle des professeurs de la Faculté des Sciences Sociales et Humanités de l’Université Souk Ahras ? - Quels sont les moyens de communication utilisés par les enseignants de la Faculté des sciences sociales et humaines de l'Université ? - Quelle est l'efficacité des moyens de communication utilisés par les enseignants de la Faculté des sciences sociales et humaines de l'Université ? Quels sont les obstacles qui entravent l'efficacité des méthodes de communication pour l'acquisition de compétences professionnelles chez les professeurs d'université ? Cette étude s'appuie sur l'approche théorique constructiviste fonctionnelle, la plus pertinente pour notre étude. Afin d'atteindre l'objectif de cette étude, nous avons utilisé l'approche descriptive car elle est compatible avec la problématique de l'étude et parce qu'elle est la plus proche de la collecte de données, de leur analyse quantitative et qualitative, et de leur interprétation dans leur contexte spécifique en utilisant un ensemble d'outils, qui est un formulaire électronique avec un format de mesure d'attitude qui comprend quatre axes avec l'axe d'information sociologique et l'outil d'observation. Après un traitement statistique et descriptif, un ensemble de résultats a été obtenu, dont les plus importants sont les suivants : - La compétence professionnelle est moyenne, avec des faiblesses en termes de suivi des progrès scientifiques et d'utilisation des technologies. - Les méthodes formelles et la communication électronique sont les plus utilisées. La communication informelle a un impact limité. - Les méthodes de communication, notamment formelles et technologiques, sont très efficaces pour améliorer les compétences professionnelles. Les obstacles psychologiques, organisationnels et techniques ont un impact significatif sur l’efficacité et l’efficience de la communication.
Keywords: الاتصال التنظيمي; الكفاءة المهنية; تحسين الأداء المهني; الأستاذ الجامعي